Diverged Effects of Piperine on Testicular Development: Stimulating Leydig Cell Development but Inhibiting Spermatogenesis in Rats - Chen, Xianwu; Ge, Fei; Liu, Jianpeng; Bao, Suhao; Chen, Yong; Li, Dongli; Li, Yong; Huang, Tongliang; Chen, Xiaofang; Zhu, Qiqi; Lian, Qingquan; Ge, Ren-Shan (Frontiers in Pharmacology, 2018)
Background: Piperine is the primary pungent alkaloid isolated from the fruit of black peppercorns. Piperine is used frequently in dietary supplements and traditional medicines. The objective of the present study was to investigate the effects of piperine on the testis development in pubertal rat. Methods: Piperine (0 or 5 or 10 mg/kg) was gavaged to 35-day-old male Sprague-Dawley rats for 30 days. Serum levels of testosterone (T), luteinizing hormone (LH), and follicle-stimulating hormone (FSH) were measured. The development of adult Leydig cell population was also analyzed on 65 days postpartum. For in vitro studies, immature Leydig cells were isolated from 35-day-old male rats and treated with 50 M piperine in the presence of different steroidogenic stimulators/substrates for 24 h. Results: Thirty-day treatment of rats with piperine significantly increased serum T levels without affecting LH concentrations. However, piperine treatment reduced serum FSH levels. Consistent with increase in serum T, piperine increased Leydig cell number, cell size and multiple steroidogenic pathway proteins, including steroidogenic acute regulatory protein, cholesterol side-chain cleavage enzyme, 3-hydroxysteroid dehydrogenase 1, 17-hydroxylase/20-lyase, and steroidogenic factor 1 expression levels. Piperine significantly increased the ratio of phospho-AKT1 (pAKT1)/AKT1, phosphos-AKT2 (pAKT2)/AKT2, and phospho-ERK1/2 (pERK1/2)/ERK1/2 in the testis. Interestingly, piperine inhibited spermatogenesis. Piperine in vitro also increased androgen production and stimulated cholesterol side-chain cleavage enzyme and 17-hydroxylase/20-lyase activities in immature Leydig cells. Conclusion: Piperine stimulates pubertal Leydig cell development by increasing Leydig cell number and promoting its maturation while it inhibits spermatogenesis in the rat. ERK1/2 and AKT pathways may involve in the piperine-mediated stimulation of Leydig cell development.